SHORT NOTICES (Reviews in religion and theology, 2004)
Books reviewed: Harold Coward, Sin and Salvation in the World Religions: A Short Introduction Alan Race and Ingrid Shafer (eds), Religions in Dialogue: From Theocracy to Democracy Melanie J. Wright, Understanding Judaism Ellen F. Davis and Richard B. Hays (eds), The Art of Reading Scripture K.A. Kitchen, On the Reliability of the Old Testament Judith Kovacs and Christopher Rowland, Revelation: The Apocalypse of Jesus Christ John Holdsworth, Dwelling in a Strange Land: Exile in the Bible and in the Church David L. Balch and Carolyn Osiek (eds), Early Christian Families in Context: An Interdisciplinary Dialogue Peter L. Berger, Questions of Faith: A Skeptical Affirmation of Christianity Andrew Pierce and Geraldine Smyth OP (eds), The Critical Spirit: Theology at the Crossroads of Faith and Culture Craig Detweiler and Barry Taylor, A Matrix of Meanings: Finding God in Popular Culture Robert W. Jenson, On Thinking the Human: Resolutions of Difficult Notions David Knight, Science and Spirituality: The Volatile Connection Natalie K. Watson, Feminist Theology Tina Beattie, Woman Burton Z. Cooper and John S. McClure, Claiming Theology in the Pulpit